Fine-grained rare earth nickel-iron alloy with high proportion of Widmanstaetten structure
Patent Information
- Application Number
- CN202610791926.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明实施例的目的是提供一种高等轴晶比例的细晶稀土镍铁合金,通过优化合金成分与含量,使合金凝固后获得柱状晶平均宽度≤50μm且等轴晶比例≥40%的细晶、高等轴晶比例组织,显著降低了构件的力学性能各向异性,解决了现有镍铁合金因粗大柱状晶导致各向异性显著的问题
1.通过在合金中引入Nb、Zr、Hf等具有特定原子半径与晶格匹配特性的固溶调控元素,显著突破了Ce、Y、Gd、Nd、Sc等稀土元素在镍铁基体中的固溶极限,使稀土以全固溶态或尺寸小于2μm、面积分数不超过1%的细小弥散第二相形式存在,DSC检测在450℃~850℃区间无稀土第二相吸热熔解峰,从而有效避免了常规工艺中微米级高熔点稀土第二相的形成,减少了增材制造、精密铸造及粉末冶金过程中的未熔合、孔隙等缺陷,大幅提升了构件的致密度与高温力学可靠性;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of non-ferrous metal alloy technology, and in particular to a fine-grained rare earth nickel-iron alloy with a high isoaxial crystal ratio. Background Technology
[0002] Nickel-iron alloys containing rare earth elements Ce, Y, Gd, Nd, and Sc have become core materials for high-end equipment such as aero-engines, gas turbines, and nuclear reactors due to their excellent high-temperature corrosion resistance, oxidation resistance, and creep strength. However, the solid solubility of these rare earth elements in nickel-iron alloys is extremely low at room temperature. Alloys prepared by conventional processes often contain a large number of micron-sized high-melting-point rare earth second phases, such as Fe2Sc, Ni5Ce, Ni3Gd, and Ni2Y. In subsequent processing such as precision casting, additive manufacturing, and powder metallurgy, these second phases can easily cause a series of process defects and degrade material properties. Specifically, these second phases are difficult to completely dissolve during the melting process, easily becoming nucleation sites for pores and unfused defects, reducing component density and severely affecting grain boundary bonding strength at high temperatures. Unmelted particles hinder melt spread and filling, forming defects in precision-cast complex components or additive manufacturing interlayers. Simultaneously, the significant differences in thermal expansion coefficients and elastic moduli between the rare earth second phases and the nickel matrix lead to continuous stress concentration at the phase interface during rapid cooling and high-temperature service cycles, inducing intergranular cracks and reducing the high-temperature fatigue life of the components. Furthermore, rare earth elements tend to segregate at grain boundaries, causing the second phase to agglomerate and grow, further weakening grain boundary properties. Moreover, when such alloys are used as rare earth additives in steelmaking, the aforementioned high-melting-point rare earth second phases are also difficult to dissolve rapidly in molten steel, affecting the rare earth yield and uniform distribution, weakening their effect on purifying molten steel and refining grains.
[0003] On the other hand, nickel-iron alloys have high melting points and poor thermal conductivity. During the preparation processes of precision casting, powder metallurgy, and additive manufacturing, the fixed heat flow direction easily leads to the formation of coarse columnar crystals that grow along the deposition direction, resulting in significant anisotropy of the mechanical properties of the components. Simultaneously, under the "rapid heating and cooling" process conditions, the diffusion of high-content alloying elements in the alloy is restricted. Besides causing compositional segregation, this also easily induces the precipitation of harmful phases such as the Laves phase, thereby weakening the alloy's high-temperature creep performance and seriously affecting its service reliability. Therefore, there is an urgent need to develop a novel rare-earth nickel-iron alloy that can effectively suppress the formation of high-melting-point rare-earth second phases, refine columnar crystals, improve compositional uniformity, and reduce the precipitation of harmful phases. Summary of the Invention
[0004] The purpose of this invention is to provide a fine-grained rare-earth nickel-iron alloy with a high equiaxed crystal ratio. By optimizing the alloy composition and content, the alloy solidifies to obtain a fine-grained, high equiaxed crystal structure with an average columnar crystal width ≤50μm and an equiaxed crystal ratio ≥40%, which significantly reduces the anisotropy of the mechanical properties of the component and solves the problem of significant anisotropy caused by coarse columnar crystals in existing nickel-iron alloys.
[0005] To solve the above technical problems, embodiments of the present invention provide a fine-grained rare-earth nickel-iron alloy with a high isoaxial crystal ratio. The fine-grained rare-earth nickel-iron alloy has a composition of Ni-Fe-RE-M, where RE is one or more of Ce, La, Sm, Dy, Y, Gd, Nd and Sc, and M is one or more of Nb, Zr, Hf, Ti, Ta, W, B, C, Co, Mo and Cr. The Ni content ranges from 20.0 wt.% to 75.0 wt.%, the Fe content ranges from 20.0 wt.% to 75.0 wt.%, the total RE content ranges from 0.001 wt.% to 0.1 wt.%, and the total M content ranges from 0.7 wt.% to 15.5 wt.%. The columnar crystals of the fine-grained rare-earth nickel-iron alloy have an average width of ≤50μm and an equiaxed crystal ratio of ≥40%.
[0006] Furthermore, in the fine-grained rare-earth nickel-iron alloy, the rare earth elements exist in a fully dissolved state or in a dissolved state coexisting with a finely dispersed second phase.
[0007] Furthermore, when a rare earth second phase is present, the size of the second phase is <2μm, the average area fraction is ≤1%, and any 1mm 2 Within the alloy region, the quantity of the second phase varies by no more than 10%.
[0008] Furthermore, the relative deviation of Al and Ti composition between any two points in the fine-grained rare-earth nickel-iron alloy is ≤3%, and the total area fraction of harmful segregating phases Laves phase and σ phase is ≤0.5%.
[0009] Furthermore, when the fine-grained rare-earth nickel-iron alloy is detected by differential scanning calorimetry, no endothermic melting peak of the rare-earth second phase is observed in the temperature range of 450℃ to 850℃.
[0010] Furthermore, the RE is one or more of Ce, Y, and Nd; The total RE content is 0.003 wt.%~0.02 wt.%.
[0011] Furthermore, M is one or more of Nb, Zr, and Hf; The Nb content is 0.1 wt.%~3.0 wt.%, the Zr content is 0.01 wt.%~0.5 wt.%, and the Hf content is 0.01 wt.%~2 wt.%.
[0012] Furthermore, M is one or more of Ti, Ta, W, B, and C; The Ti content is 0.05 wt.%~1 wt.%, the Ta content is 0.05 wt.%~3 wt.%, the W content is 0.005 wt.%~0.02 wt.%, the B content is 0.0005 wt.%~0.01 wt.%, and the C content is 0.01 wt.%~1.5 wt.%.
[0013] Furthermore, M is one or more of Co, Mo, and Cr; The Co content is 0.01 wt.%~3 wt.%, the Mo content is 0.02 wt.%~6 wt.%, and the Cr content is 0.02 wt.%~10 wt.%, with Co:Mo = 1:2~1:10, Co:Cr = 1:2~1:20, and Mo:Cr = 1:1~1:5.
[0014] The above-described technical solutions of the embodiments of the present invention have the following beneficial technical effects: 1. By introducing solid solution regulating elements such as Nb, Zr, and Hf with specific atomic radii and lattice matching characteristics into the alloy, the solid solution limits of rare earth elements such as Ce, Y, Gd, Nd, and Sc in the nickel-iron matrix are significantly broken. This allows rare earth elements to exist in a fully solid solution state or as fine and dispersed second phases with a size of less than 2 μm and an area fraction of no more than 1%. DSC detection shows no endothermic melting peak of rare earth second phase in the range of 450℃ to 850℃, thus effectively avoiding the formation of micron-sized high-melting-point rare earth second phases in conventional processes. This reduces defects such as incomplete fusion and porosity in additive manufacturing, precision casting, and powder metallurgy processes, and significantly improves the density and high-temperature mechanical reliability of components. 2. By rationally adding rare earth elements such as La, Sm, and Dy, as well as grain-regulating elements such as Ti, Ta, W, B, and C, and utilizing compositional supercooling and heterogeneous nucleation effects, the average width of columnar crystals after alloy solidification is controlled within 50 μm, and the proportion of equiaxed crystals reaches more than 40%, resulting in a fine-grained microstructure with a high proportion of equiaxed crystals. This significantly reduces the anisotropy of mechanical properties caused by coarse columnar crystals and improves the service stability and overall reliability of components under complex stress conditions. 3. By optimizing the addition ratios of Co, Mo, and Cr to meet the requirements of Co:Mo = 1:2~1:10, Co:Cr = 1:2~1:20, and Mo:Cr = 1:1~1:5, the distribution coefficients of Al and Ti during solidification were effectively controlled. This ensured that the relative deviation of Al and Ti composition between any two points in the alloy did not exceed 3%, while the total area fraction of harmful segregated phases such as Laves phase and σ phase was controlled below 0.5%. This significantly improved the compositional uniformity of the alloy, delayed the precipitation kinetics of harmful phases, and thus enhanced the high-temperature creep performance and long-term service stability of the alloy. Detailed Implementation
[0015] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of the invention.
[0016] This invention provides a fine-grained rare-earth nickel-iron alloy with a high equiaxed crystal ratio. The alloy composition is Ni-Fe-RE-M, where RE is one or more of Ce, La, Sm, Dy, Y, Gd, Nd, and Sc, and M is one or more of Nb, Zr, Hf, Ti, Ta, W, B, C, Co, Mo, and Cr. The Ni content is 20.0 wt.%~75.0 wt.%, the Fe content is 20.0 wt.%~75.0 wt.%, the total RE content is 0.001 wt.%~0.1 wt.%, and the total M content is 0.7 wt.%~15.5 wt.%. The average width of the columnar crystals in the fine-grained rare-earth nickel-iron alloy is ≤50 μm, and the equiaxed crystal ratio is ≥40%.
[0017] The chemical composition of this fine-grained rare-earth nickel-iron alloy is represented as Ni-Fe-RE-M, where Ni and Fe are the matrix elements, with Ni content ranging from 20.0 wt.% to 75.0 wt.% and Fe content ranging from 20.0 wt.% to 75.0 wt.%. This wide range allows the alloy to flexibly adjust the nickel-iron ratio according to different service conditions, ensuring sufficient matrix strength and corrosion resistance while balancing cost and processing performance. RE represents one or more rare-earth elements, with the total content controlled within an extremely low range of 0.001 wt.% to 0.1 wt.%. This low content allows the rare-earth elements to exert their beneficial effects of purifying grain boundaries and microalloying strengthening, while avoiding the formation of a large amount of high-melting-point rare-earth second phases due to solid solution saturation caused by excessive rare-earth elements. M represents one or more alloying elements, with the total content ranging from 0.7 wt.% to 15.5 wt.%. This range ensures sufficient solid solution strengthening, grain control, and harmful phase suppression effects, while not significantly impairing the alloy's plastic processing ability.
[0018] Rare earth elements (REs) are selected from one or more of Ce, La, Sm, Dy, Y, Gd, Nd, and Sc. These rare earth elements have unique electronic structures and large atomic radii, which can generate a strong tendency for grain boundary segregation in nickel-iron matrices, thereby filling grain boundary vacancies, reducing grain boundary energy, and preventing the enrichment of impurity elements at grain boundaries. When the total rare earth content does not exceed 0.1 wt.%, most rare earth atoms can be dissolved in the nickel-iron matrix lattice, with only a very small amount existing in the form of submicron-sized dispersed phases. This "low content, high solid solution" approach allows rare earths to melt rapidly and distribute uniformly in subsequent rapid solidification processes (such as additive manufacturing and precision casting), avoiding the formation of micron-sized high-melting-point rare earth intermetallic compounds (such as Fe2Sc and Ni5Ce) due to excessively low rare earth solid solubility in conventional processes, thus significantly reducing nucleation sites for defects such as incomplete fusion and porosity.
[0019] The element M is selected from one or more of Nb, Zr, Hf, Ti, Ta, W, B, C, Co, Mo, and Cr, with a total content of 0.7 wt.% to 15.5 wt.%. These elements play multiple roles in the alloy: on the one hand, elements such as Nb, Zr, and Hf, with specific atomic radii and electronic configurations, can preferentially dissolve in the nickel-iron matrix, regulating the lattice constant and electronic distribution state of the matrix, thereby improving the occupancy stability of rare earth solute atoms in the lattice and inhibiting the precipitation of rare earth elements to form coarse second phases; on the other hand, elements such as Ti, Ta, W, B, and C can produce significant compositional undercooling effects and provide heterogeneous nucleation sites, thereby refining the solidification structure; in addition, elements such as Co, Mo, and Cr, through reasonable proportioning, can affect the solute partition coefficient, improve compositional uniformity, and delay the precipitation of harmful phases. Controlling the total content of element M above 0.7 wt.% ensures that the above-mentioned regulatory effects are fully realized, while below 15.5 wt.% avoids over-alloying leading to the formation of brittle phases or processing difficulties.
[0020] The alloy of this invention exhibits a typical fine-grained microstructure after solidification using conventional processes. Specifically, the average width of the columnar crystals does not exceed 50 micrometers, and the area occupied by equiaxed crystals is not less than 40%. This microstructure is achieved through the introduction of rare earth elements such as La, Sm, and Dy, as well as grain-regulating elements such as Ti, Ta, W, B, and C. During solidification, these elements accumulate at the solid-liquid interface front, resulting in strong compositional supercooling, which promotes the formation of a large number of new crystal nuclei at the interface front. Simultaneously, some high-melting-point particles (such as carbides and borides) can act as heterogeneous nucleation sites, further increasing the nucleus density. The synergistic effect of compositional supercooling and heterogeneous nucleation effectively suppresses the development of coarse columnar crystals growing along the heat flow direction, instead forming a large number of fine equiaxed crystals. Compared to the columnar crystals with widths reaching hundreds of micrometers commonly found in traditional nickel-iron alloys, this invention controls the width of the columnar crystals to below 50 micrometers and increases the proportion of equiaxed crystals to over 40%, significantly reducing the sensitivity of mechanical properties to direction caused by anisotropy in crystal growth.
[0021] This alloy is particularly suitable for advanced manufacturing processes characterized by rapid melting and solidification, such as precision casting, additive manufacturing (e.g., selective laser melting, electron beam melting), and powder metallurgy. In these processes, the melt undergoes extremely high cooling rates and temperature gradients, easily leading to the formation of coarse columnar crystals and compositional segregation. This invention, through the aforementioned compositional design, enables the alloy to spontaneously acquire a fine-grained microstructure with a high proportion of isometric grains under conventional solidification conditions (i.e., without special external treatments or extreme cooling conditions). In other words, this alloy exhibits excellent process robustness, requiring no additional complex grain refinement processes (such as adding grain refiners, applying ultrasonic vibration, or mechanical stirring), and can stably obtain the target microstructure during conventional casting, powder preparation, or additive manufacturing processes. This reduces production costs and improves batch consistency of component quality.
[0022] Specifically, in fine-grained rare-earth nickel-iron alloys, rare earth elements exist in either a fully dissolved state or a state coexisting with finely dispersed second phases. When a rare-earth second phase is present, the size of the second phase is <2μm, the average area fraction is ≤1%, and the dispersion of the quantity of the second phase within any 1mm² alloy region does not exceed 10%.
[0023] In this invention, rare earth elements can exist in two forms in the alloy: one is a fully dissolved state, where rare earth atoms are completely dissolved in the lattice of the nickel-iron matrix through substitution or interstitial processes, without forming any independent compound phase; the other is a coexistence of the dissolved state and fine, dispersed second phases, where most rare earth elements remain dissolved in the matrix, with only a small amount forming extremely fine intermetallic compounds or carbides with nickel, iron, or nitrogen (M) elements. This dual-form design is based on overcoming the limits of rare earth solid solubility. In conventional alloys, the solid solubility of rare earth elements is extremely low, with almost all precipitating as coarse second phases; however, this invention, by introducing solid solution regulating elements such as Nb, Zr, and Hf, improves the lattice occupancy stability of rare earth elements in the nickel-iron matrix, allowing them to exist primarily in a dissolved state. Even if local compositional fluctuations or solidification kinetics lead to the precipitation of a small amount of second phase, its size and quantity are strictly limited to extremely low levels, without substantially harming the alloy's properties.
[0024] When rare-earth second phases are unavoidably present in the alloy, this invention requires that their maximum size not exceed 2 micrometers. In typical rapid solidification processes (such as molten pool solidification in additive manufacturing), particles smaller than 2 micrometers can be pushed away by the solid-liquid interface instead of becoming heterogeneous nucleation sites, or undergo complete re-dissolution during subsequent thermal cycling. Simultaneously, the degree of interfacial stress concentration caused by the difference in thermal expansion coefficients between the submicron to 2-micrometer-sized second phase and the nickel-iron matrix is significantly lower than that caused by micrometer-sized coarse second phases. Experiments show that when the size of the second phase decreases from several micrometers to below 2 micrometers, the peak stress at the phase interface can be reduced by several times, thereby effectively avoiding intergranular microcracks induced by thermal mismatch during cooling or service. This invention, by suppressing the strong segregation of rare earth elements to grain boundaries and controlling solidification kinetics, restricts any possible precipitated rare-earth second phases to the submicron to 2-micrometer range.
[0025] The average area fraction of the rare earth second phase is no higher than 1%, and even if a second phase exists, its area proportion on any polished cross section is almost negligible. The primary benefit of this low area fraction is that the majority of rare earth elements (more than 99% of the mass fraction) exist in a solid solution state within the matrix, thus fully leveraging the strengthening effect of rare earth solid solution, including increasing lattice distortion energy, pinning dislocations, and purifying grain boundaries. Secondly, the extremely small total area occupied by the second phase reduces potential sites for grain boundary slip and void nucleation during high-temperature creep. Thirdly, in the melting stage of additive manufacturing or precision casting, such a low content of the second phase can completely dissolve in the melt in a very short time, without leaving unmelted particles that hinder melt spread or become porosity nucleation sites. Therefore, an area fraction ≤1% is a quantitative guarantee to ensure that rare earth elements are predominantly in a solid solution state and to avoid the negative impacts of the second phase.
[0026] Within any 1 square millimeter alloy region, the dispersion range of the rare-earth second phase quantity (i.e., the relative fluctuation range of the second phase quantity in different regions) does not exceed 10%, a characteristic that reflects the highly uniform distribution of the second phase at the microscale. In conventional rare-earth nickel-iron alloys, due to the strong segregation of rare earth elements towards grain boundaries, the second phase often agglomerates and grows at the grain boundaries, resulting in a much higher density of the second phase in the grain boundary region than within the grains, leading to severe uneven distribution. This invention improves the occupancy stability of rare earth elements in the crystal lattice by adding elements such as Nb, Zr, and Hf, weakening the driving force for rare earth diffusion towards grain boundaries. At the same time, the fine-grained structure provides a large number of intragranular nucleation sites, allowing any small amount of second phase that may precipitate to be uniformly dispersed within the grains and at the grain boundaries, avoiding local agglomeration. A dispersion range of ≤10% means that the difference in the quantity of the second phase between any two 1 mm² regions is extremely small, thereby eliminating the risk that local second-phase enrichment areas become preferential crack initiation channels and ensuring the consistency of the overall mechanical properties of the component.
[0027] The aforementioned control over the size, area fraction, and distribution uniformity of the second phase is not achieved independently, but is closely related to the solidification kinetics of the alloy under rapid melting and solidification conditions. In precision casting, additive manufacturing, or powder metallurgy processes, the melt undergoes extremely high cooling rates (up to 10⁻⁶). 3 ~10 6 The invention addresses the issue of rare earth atoms (K / s) and temperature gradients. In conventional alloys, rare earth atoms do not have sufficient time to diffuse and tend to accumulate between dendrites or at grain boundaries, forming coarse second phases. This invention, by controlling the matrix composition (especially by adding elements such as Nb, Zr, and Hf), alters the distribution and diffusion coefficients of rare earth atoms at the solid-liquid interface, allowing rare earth atoms to be more uniformly embedded in the growing solid phase, thereby suppressing the coarsening of the second phase. Simultaneously, the introduction of fine heterogeneous nucleation particles (such as carbides and borides) into the alloy provides a uniform nucleation substrate for rare earths, promoting the precipitation of any unavoidable second phase in a fine, dispersed, and equidistant manner, rather than agglomerating at specific locations. Therefore, the aforementioned control indicators for size, area fraction, and dispersion amplitude are, in fact, a comprehensive manifestation of the successful achievement of "high solid solution, low precipitation, and uniform distribution" at the solidification kinetics level through the alloy composition design of this invention.
[0028] Furthermore, the relative deviation of Al and Ti composition between any two points in the fine-grained rare-earth nickel-iron alloy is ≤3%, and the total area fraction of harmful segregating phases Laves phase and σ phase is ≤0.5%.
[0029] This invention further proposes strict control over the compositional uniformity of Al and Ti, two key elements, and the content of harmful segregated phases in alloys. In nickel-iron alloys, Al and Ti are common strengthening phase-forming elements. However, if diffusion is restricted during solidification, especially under the conditions of "rapid heating and cooling" in additive manufacturing or precision casting, Al and Ti are prone to segregation between dendrites or at grain boundaries. This leads to a significant deviation of local composition from nominal values, which in turn induces the precipitation of harmful topologically close-packed phases such as Laves phase and σ phase. These harmful phases have complex crystal structures and brittle characteristics, significantly reducing the high-temperature creep performance and plasticity of the alloy. To address this, this invention effectively controls the solute distribution coefficients of Al and Ti during solidification by optimizing the proportions of alloying elements such as Co, Mo, and Cr. This makes the redistribution behavior of the two at the solid-liquid interface more uniform, thereby controlling the relative deviation of Al and Ti composition between any two points to within 3%. From the macroscopic component to the microscopic dendrite scale, the concentration distribution of Al and Ti achieves high uniformity, eliminating the microstructure inhomogeneity caused by local enrichment or depletion. Meanwhile, due to the significant suppression of segregation, the harmful precipitation of the Laves and σ phases is also effectively delayed, with their total area fraction limited to below 0.5%. This means that the area proportion of these brittle phases in the entire alloy cross-section is almost negligible, thus preventing them from acting as crack initiation sources or rapid propagation channels and causing destructive effects on mechanical properties. Through the dual control of compositional homogeneity and harmful phase content, the alloy of this invention can maintain the consistency and purity of its microstructure even after rapid solidification, providing a crucial guarantee for its long-term reliability under high-temperature and high-stress service environments.
[0030] Furthermore, when the fine-grained rare-earth nickel-iron alloy was detected by differential scanning calorimetry, no endothermic melting peak of the rare-earth second phase was observed in the temperature range of 450℃ to 850℃.
[0031] When performing thermal analysis on the alloy using differential scanning calorimetry (DSC), no endothermic melting peaks related to the rare earth second phase appeared in the temperature range of 450℃ to 850℃. This thermal analysis characteristic directly reflects the occurrence state of rare earth in the alloy: when rare earth exists in a fully solid-solid state in the nickel-iron matrix lattice, there are naturally no corresponding melting or phase transformation endothermic peaks since there are no independent rare earth compound phases; when rare earth coexists in a solid-solid state with a very small amount of fine, dispersed second phase, since the size of the second phase is usually less than 2 micrometers and the area fraction is less than 1%, the thermal effect corresponding to its melting or dissolution is extremely weak. In addition, these fine second phases may have low melting points or the temperature at which solid solution re-dissolution occurs is below 450℃. Therefore, no obvious endothermic peaks that can be detected by DSC can be formed in the detection range above 450℃. Compared to the micron-sized high-melting-point rare-earth intermetallic compounds (such as Fe2Sc, Ni5Ce, Ni3Gd, Ni2Y, etc.) commonly found in conventional rare-earth nickel-iron alloys, these coarse second phases typically exhibit significant thermal effect peaks in the 500℃ to 800℃ range. However, the alloy of this invention shows no endothermic peaks throughout the 450℃ to 850℃ range, thermodynamically verifying that the high-melting-point rare-earth second phase has been effectively suppressed. This characteristic not only provides a simple and non-destructive testing method but also indirectly proves that this invention successfully overcomes the solid solution limit of rare earths in the nickel-iron matrix by introducing solid solution regulating elements such as Nb, Zr, and Hf. This ensures that the rare earth matrix exists in a beneficial fully solid-solid state or an extremely fine dispersed state, thereby avoiding process defects such as incomplete fusion, porosity, and intergranular cracks caused by coarse rare-earth second phases in conventional alloys. This provides a key quality criterion for the stable forming and reliable service of the alloy in high-end manufacturing processes.
[0032] Further, RE is one or more of Ce, Y and Nd; wherein the total RE content is 0.003 wt.%~0.02 wt.%.
[0033] The types and contents of rare earth elements were further optimized and limited, specifically, RE was selected from one or more of Ce, Y, and Nd, with the total content controlled between 0.003 wt.% and 0.02 wt.%. Ce, Y, and Nd are the most common and effective rare earth strengthening elements in nickel-iron alloys. They have a strong tendency to agglomerate at grain boundaries in the nickel-iron matrix, effectively filling grain boundary vacancies and pinning grain boundary migration, thus playing an excellent role in grain boundary purification and microalloying strengthening. At the same time, these three rare earth elements have a high affinity for impurity elements such as oxygen and sulfur, and can form stable rare earth oxides or sulfides, reducing the harmful effects of impurities on grain boundaries. Compared with other rare earth elements such as La, Sm, and Dy, the solid solution behavior of Ce, Y, and Nd in nickel-iron alloys is more controllable, making it easier to achieve a synergistic effect of grain boundary strengthening and precipitation strengthening, and significantly improving the high-temperature creep performance and oxidation resistance of the alloy. Regarding the content, the present invention further narrows the preferred range to 0.003 wt.% to 0.02 wt.%. This range ensures that a sufficient concentration of rare earth atoms plays a purifying and strengthening role at the grain boundaries, while avoiding the risk of local solid solution saturation and a small amount of second phase precipitation that may result from excessively high rare earth content (e.g., close to the upper limit of 0.1 wt.%). In other words, this preferred content range is the best balance between sufficient benefit and avoiding excess, ensuring that rare earth elements exist in the matrix in a fully solid solution state or in a very small dispersed state, thereby maximizing the beneficial effects of rare earth without causing any process defects or performance degradation due to the second phase.
[0034] In one specific embodiment of the present invention, M is one or more of Nb, Zr and Hf; wherein the Nb content is 0.1 wt.%~3.0 wt.%, the Zr content is 0.01 wt.%~0.5 wt.%, and the Hf content is 0.01 wt.%~2 wt.%.
[0035] In one specific embodiment of the present invention, the M element in the alloy is further preferably one or more of Nb, Zr, and Hf, and the content range of each element is precisely defined. Nb, Zr, and Hf belong to high-melting-point transition metals and have atomic sizes similar to nickel and iron but different electronic configurations. They play a core role in "solid solution regulation" in the present invention. Specifically, these elements can preferentially dissolve in the lattice of the nickel-iron matrix. By changing the lattice constant and electronic distribution state of the matrix, they significantly improve the occupancy stability of rare earth solute atoms (such as Ce, Y, Nd, etc.) in the lattice, thereby effectively suppressing the segregation of rare earth atoms to grain boundaries and the precipitation of coarse high-melting-point intermetallic compounds. Controlling the Nb content within the range of 0.1 wt.% to 3.0 wt.% ensures sufficient driving force for solid solution regulation without causing excessive lattice distortion or precipitation of brittle Nb-rich phases; below 0.1%, the effect is not obvious, and above 3.0%, harmful Laves phases may be formed or the plasticity of the alloy may be reduced. The Zr content range is set at 0.01 wt.% to 0.5 wt.%. Zr has a strong grain refining effect and can form high-melting-point ZrC or ZrN particles as heterogeneous nucleation cores during solidification. At the same time, its microalloying effect can further stabilize the solid solution state of rare earth elements in the matrix. Due to the high reactivity of Zr, excessive addition will form coarse oxides or consume too much carbon, so the upper limit is controlled at 0.5%. The Hf content range is 0.01 wt.% to 2 wt.%. Hf is similar to Zr in chemical properties but has a larger atomic mass, and its solid solution strengthening effect is more significant. Moreover, the carbides or nitrides formed by Hf have extremely high thermal stability and can pin grain boundaries and inhibit grain growth during high-temperature service. However, Hf has a high cost and high density, so the upper limit is set at 2% to balance economy and performance. When two or three of Nb, Zr, and Hf are added in combination, they produce a synergistic effect: Nb mainly regulates the matrix lattice, Zr strengthens heterogeneous nucleation, and Hf improves high-temperature stability. The combined effect of the three can increase the solid solution limit of rare earth elements in nickel-iron matrix to several times that of conventional alloys, thereby ensuring that rare earth elements exist in a fully solid solution state or an extremely fine dispersed state, fundamentally eliminating the process defects and performance degradation caused by the micron-sized high-melting-point rare earth second phase.
[0036] In another specific embodiment of the present invention, M is one or more of Ti, Ta, W, B, and C; wherein the Ti content is 0.05 wt.%~1 wt.%, the Ta content is 0.05 wt.%~3 wt.%, the W content is 0.005 wt.%~0.02 wt.%, the B content is 0.0005 wt.%~0.01 wt.%, and the C content is 0.01 wt.%~1.5 wt.%.
[0037] In another specific embodiment of the present invention, element M is further selected from one or more of Ti, Ta, W, B, and C, and the content range of each is precisely defined. Ti, Ta, and W are high-melting-point carbide-forming elements, while B and C are interstitial atoms. They mainly play the role of grain regulation and grain boundary strengthening in the alloy. Specifically, Ti and Ta can form high-melting-point carbide or nitride particles during solidification. These particles act as heterogeneous nucleation nuclei at the solid-liquid interface front, significantly increasing the nucleus density, thereby promoting the formation of equiaxed crystals and inhibiting the growth of coarse columnar crystals. At the same time, Ti and Ta are partially dissolved in the matrix, which can produce a solid solution strengthening effect. The present invention controls the Ti content between 0.05 wt.% and 1 wt.%, and the Ta content between 0.05 wt.% and 3 wt.%. This range ensures a sufficient number of nucleation particles while avoiding the precipitation of coarse primary carbides or brittle phases due to excessive addition, which would reduce the alloy's plasticity. The content of W is set at 0.005 wt.% to 0.02 wt.%, which is a trace addition. W atoms have a large atomic radius and a high melting point, and can be dissolved in the nickel-iron matrix by substitution, resulting in significant lattice distortion strengthening. At the same time, the segregation of W at the grain boundaries can inhibit grain boundary migration and further improve the high-temperature creep resistance. Since W has a high density and high cost, a trace addition can achieve a significant effect, while adding more than 0.02% may cause local segregation or brittleness. As interstitial atoms, boron (B) and carbon (C) have a strong tendency to agglomerate at grain boundaries, filling grain boundary vacancies and pinning grain boundary slip, thus significantly strengthening grain boundaries. The B content is controlled in an extremely low range of 0.0005 wt.% to 0.01 wt.%, because B has extremely low solid solubility in nickel-iron alloys. Excessive B will form brittle boride films at grain boundaries, severely damaging grain boundary bonding. The C content is 0.01 wt.% to 1.5 wt.%. In addition to its grain boundary strengthening effect, C can also form dispersed carbide particles with Ti, Ta, W, etc. These carbides can both act as heterogeneous nucleation cores to refine grains and pin dislocations and grain boundaries during high-temperature service, improving creep resistance. When two or more of the above elements are added in combination, a synergistic effect is produced: the carbides formed by Ti, Ta, and W provide a nucleation substrate, while B and C strengthen the grain boundaries and regulate the compositional supercooling at the solidification front. Together, they reduce the average width of columnar crystals to below 50 micrometers and increase the proportion of equiaxed crystals to above 40%, thereby significantly improving the anisotropy resistance and high-temperature service reliability of the alloy.
[0038] In another specific embodiment of the present invention, M is one or more of Co, Mo and Cr; wherein the Co content is 0.01 wt.%~3 wt.%, the Mo content is 0.02 wt.%~6 wt.%, the Cr content is 0.02 wt.%~10 wt.%, and the Co:Mo = 1:2~1:10, the Co:Cr = 1:2~1:20, and the Mo:Cr = 1:1~1:5.
[0039] In another specific embodiment of the present invention, element M further comprises one or more of Co, Mo, and Cr, and the content of each and the ratio between them are finely optimized. Co, Mo, and Cr are all common solid solution strengthening elements in nickel-iron alloys, but the target of the control of their proportions in the present invention is not only traditional solid solution strengthening, but also focuses on improving the distribution behavior of solute atoms to address the compositional segregation and precipitation of harmful phases caused by the limited diffusion of elements such as Al and Ti under the "rapid cooling and heating" process conditions. Specifically, the Co content is controlled at 0.01 wt.% to 3 wt.%, Co and Ni can form an infinite solid solution, which can stabilize the face-centered cubic structure of the matrix, increase the stacking fault energy, and promote the cross-slip of dislocations, thereby improving the high-temperature plasticity of the alloy; at the same time, Co can reduce the segregation tendency of Al and Ti between dendrites. The Mo content is 0.02 wt.% to 6 wt.%, Mo is a strong solid solution strengthening element, and its large atomic radius can produce significant lattice distortion. At the same time, Mo can delay the coarsening of carbides and suppress the precipitation kinetics of harmful topologically close-packed phases. The Cr content ranges from 0.02 wt.% to 10 wt.%, primarily imparting oxidation and hot corrosion resistance to the alloy and forming a dense Cr2O3 oxide film on the matrix surface. However, simply limiting the content range of each component is insufficient to fully leverage their synergistic effect. Therefore, this invention further defines their mass ratios: Co:Mo = 1:2–1:10, Co:Cr = 1:2–1:20, and Mo:Cr = 1:1–1:5. The essence of this ratio system lies in regulating the solute partition coefficients of Al and Ti during solidification. When the proportions of Co, Mo, and Cr fall within this range, they collectively alter the diffusion field and temperature gradient at the solid-liquid interface front, causing Al and Ti atoms to tend to enter the solid phase rather than accumulate in the liquid phase, thereby significantly suppressing the formation of interdendritic segregation. Simultaneously, this ratio range precisely avoids the precipitation windows of the Laves and σ phases on the phase diagram, meaning that the nucleation and growth kinetics of these harmful phases are significantly delayed, making it difficult for them to precipitate to a harmful size or quantity within a finite time, even after rapid solidification. By controlling the content and proportion as described above, this invention ensures that the relative deviation of Al and Ti composition between any two points in the alloy does not exceed 3%, and the total area fraction of Laves phase and σ phase is limited to below 0.5%. Thus, without sacrificing high-temperature strength, the compositional uniformity, microstructure consistency and long-term service stability of the alloy are significantly improved.
[0040] Below, this invention prepared rare-earth nickel-iron alloys with different compositions using a vacuum induction melting method. The composition of each alloy was analyzed, its microstructure was characterized, DSC thermal analysis was performed, compositional homogeneity was tested, the ratio of columnar to equiaxed crystals was statistically analyzed, and harmful phases were identified. Simultaneously, using each alloy as raw material, selective laser melting (SLM) and precision casting experiments were conducted. The area fractions of defects such as incomplete fusion, porosity, and cracks in each formed part were compared and statistically analyzed, and the mechanical properties were also statistically analyzed. The methods for preparing alloy samples, finished parts, and conducting testing are as follows: Alloy sample preparation: Pure nickel (99.9%), pure iron (99.9%), pure cobalt (99.9%), pure molybdenum (99.9%), pure chromium (99.9%), and intermediate alloys such as Ni-RE, Ni-Nb, Ni-Zr, Ni-Hf, Ni-Ti, Ni-Ta, Ni-W, Ni-B, and Ni-C were used as raw materials, weighed and batched according to the designed composition. Melting was carried out in a vacuum induction furnace at a temperature of 1500–1650℃, with argon protection throughout to prevent oxidation. After refining, the melt was used to prepare the alloy through gravity casting, gas atomization powdering, and rotating electrode powdering processes.
[0041] Microstructure characterization of alloy samples: Polished cross-sections of each alloy were observed using field emission scanning electron microscopy (FE-SEM), and the chemical composition, grain size, and columnar / equiaxed crystal ratio of the second phase were determined using energy dispersive spectroscopy (EDS) and electron backscatter diffraction (EBSD). The maximum size, average size, and area fraction of the rare earth second phase were quantitatively analyzed using Image-Pro Plus image analysis software, and the area fractions of the Laves and σ phases were statistically analyzed.
[0042] Method for testing the dispersion of the number of second-phase particles per unit area in the alloy: Field emission scanning electron microscopy (FE-SEM) was used in backscattered electron (BSE) mode. Five different fields of view were randomly selected, each with an area of 0.1 mm × 0.1 mm (i.e., 0.01 mm²), and high-resolution photomicrographs (≥5000×) were taken. Image-Pro Plus or Nano Measurer image analysis software was used for automatic identification and manual verification counting of the second-phase particles in each photograph. The total number of second-phase particles in each field of view was recorded. The maximum number of second-phase particles (N) in the five fields of view was calculated. max ) and minimum value (N) min The dispersion amplitude (D) of the number of second phases per unit area is calculated using the following formula: D = (N max - N min ) / N avg Thermal analysis of alloy samples: Differential scanning calorimetry (DSC) was performed under an argon atmosphere at a heating rate of 10℃ / min, with a detection range of 25–1200℃. The focus was on observing whether endothermic melting peaks of the rare earth second phase appeared in the 450–850℃ range to determine the state of the rare earth elements.
[0043] Composition uniformity analysis: Samples were taken from different parts (top, middle, bottom, left, right) of the ingot or formed part, and the Al and Ti contents were determined by electron probe microanalysis (EPMA) or ICP-OES. The maximum relative deviation between any two points was calculated.
[0044] Columnar and equiaxed crystal analysis: The solidification structure of the alloy was analyzed using an optical microscope (OM), and the average width of columnar crystals and the area ratio of equiaxed crystals were statistically analyzed.
[0045] Additive manufacturing preparation test: Using alloy powder obtained by gas atomization as raw material, forming tests were conducted on a selective laser melting (SLM) device. Laser power: 250–400W; scanning speed: 800–1200mm / s; layer thickness: 30–50μm; scanning spacing: 0.1–0.12mm; substrate preheated to 150–250℃. Precision casting preparation test: Using investment casting technology, the alloy melt was poured into a ceramic mold preheated to 800–1000℃ to obtain castings with complex structures.
[0046] Forming quality: After SLM and precision casting, the cross-section and longitudinal section are observed by SEM, and non-destructive testing and Image-Pro Plus software are used to count the area fraction of defects such as incomplete fusion, porosity, and cracks.
[0047] Mechanical property testing: Standard plate-shaped tensile specimens (refer to GB / T 228.1-2021) were cut from SLM formed parts and precision casting parts respectively. Tensile tests were carried out using a universal testing machine at room temperature and high temperature. At least 3 valid specimens were tested for each component and the average value was taken to calculate the tensile strength and elongation after fracture.
[0048] Comparative Example 1 The alloy was precisely formulated according to mass percentages, with Ni content of 61.0%, Fe content of 38.5%, Ce content of 0.001%, Mo content of 0.1%, and Cr content of 0.01%. Raw materials included pure nickel, pure iron, Ni-Ce master alloy, pure molybdenum, and pure chromium. Melting was carried out in a vacuum induction furnace at 1550℃ under argon protection throughout the process. The melt was refined and then atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was employed, with process parameters consistent with Example 1. The SLM-formed parts were tested for compositional uniformity, the columnar / equiaxed crystal ratio was statistically analyzed, and the area fraction of harmful phases was determined. The test results show that the maximum size of the second phase of the alloy is 3.8 μm, the area fraction of the second phase is 2.80%, the DSC curve has obvious endothermic peaks in the range of 450~850℃, the average width of columnar crystals is 85 μm, the proportion of equiaxed crystals is only 5%, the Al / Ti composition deviation is 6.8%, the Laves / σ phase area fraction is 1.85%, the defect area fraction is 0.95%, the tensile strength is 520 MPa, and the elongation is 8%.
[0049] Comparative Example 2 The alloy was precisely formulated according to mass percentages, with Ni content of 48.0%, Fe content of 44.8%, Y content of 0.003%, Mo content of 2.0%, and Cr content of 5.0%. Raw materials included pure nickel, pure iron, Ni-Y master alloy, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1560℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. SLM forming was used, with process parameters consistent with Example 1. The SLM-formed parts were tested for compositional uniformity, the columnar / equiaxed crystal ratio was statistically analyzed, and the area fraction of harmful phases was determined. The test results show that the maximum size of the second phase of the alloy is 2.8 μm, the area fraction of the second phase is 1.95%, the DSC curve has obvious endothermic peaks in the range of 450~850℃, the average width of columnar crystals is 78 μm, the proportion of equiaxed crystals is 12%, the Al / Ti composition deviation is 7.5%, the Laves / σ phase area fraction is 1.50%, the defect area fraction is 0.78%, the tensile strength is 580 MPa, and the elongation is 12%.
[0050] Comparative Example 3 The alloy was precisely formulated according to mass percentages, with Ni content of 49.0%, Fe content of 48.0%, Y content of 0.008%, Ti content of 1.2% (outside the scope of this invention), B content of 0.02% (outside the scope of this invention), Co content of 0.05%, Mo content of 0.3%, and Cr content of 0.5%. Raw materials selected included pure nickel, pure iron, Ni-Y master alloy, Ni-Ti master alloy, Ni-B master alloy, pure cobalt, pure molybdenum, and pure chromium. Vacuum induction melting was performed at 1570℃ under argon protection, followed by refining and gas atomization to form powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. A precision casting process was employed, with parameters consistent with Example 3. The castings were tested for compositional uniformity, the columnar / equiaxed crystal ratio was statistically analyzed, and the area fraction of harmful phases was determined. The test results show that the maximum size of the second phase of the alloy is 1.8 μm, the area fraction of the second phase is 1.20%, the DSC curve has obvious endothermic peaks in the range of 450~850℃, the average width of columnar crystals is 72 μm, the proportion of equiaxed crystals is 18%, the Al / Ti composition deviation is 7.2%, the Laves / σ phase area fraction is 1.20%, the defect area fraction is 0.58%, the tensile strength is 640 MPa, and the elongation is 15%.
[0051] Comparative Example 4 The alloy was precisely formulated according to mass percentages, with Ni content of 56.6%, Fe content of 42.5%, Nd content of 0.005%, Co content of 0.05% (below the lower limit of this invention), and Mo content of 0.05% (below the lower limit of this invention). Raw materials included pure nickel, pure iron, Ni-Nd master alloy, pure cobalt, and pure molybdenum. The alloy was vacuum induction melted at 1580℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. SLM forming was used, with process parameters consistent with Example 4. The SLM-formed parts were tested for compositional uniformity, the columnar / equiaxed crystal ratio was statistically analyzed, and the area fraction of harmful phases was determined. The test results show that the maximum size of the second phase of the alloy is 2.2 μm, the area fraction of the second phase is 1.60%, the DSC curve has obvious endothermic peaks in the range of 450~850℃, the average width of columnar crystals is 80 μm, the proportion of equiaxed crystals is 15%, the Al / Ti composition deviation is 6.9%, the Laves / σ phase area fraction is 1.35%, the defect area fraction is 0.68%, the tensile strength is 610 MPa, and the elongation is 10%.
[0052] Example 1 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 75.0%, Fe 24.295%, Ce 0.001%, Nb 0.1%, Zr 0.01%, Hf 0.4195%, Ti 0.05%, Ta 0.07%, B 0.0005%, Co 0.01%, Mo 0.02%, and Cr 0.02%. The raw materials used were pure nickel, pure iron, Ni-Ce master alloy, Ni-Nb master alloy, Ni-Zr master alloy, Ni-Hf master alloy, Ni-Ti master alloy, Ni-Ta master alloy, Ni-B master alloy, pure cobalt, pure molybdenum, and pure chromium. Melting was carried out in a vacuum induction furnace at 1550℃ under argon protection throughout the process. After refining, the melt was atomized to prepare spherical powder with a particle size distribution of 15μm~53μm. SEM, EDS, and DSC analyses were performed on the powder to detect the characteristics of the second phase and the thermal effects at 450℃~850℃. SLM forming was used with a laser power of 300W, a scanning speed of 1000mm / s, a layer thickness of 30μm, and a scanning spacing of 0.1mm. The substrate was preheated to 200℃. Compositional uniformity tests, columnar / equiaxed crystal ratio statistics, and harmful phase area fraction determination were performed on the SLM-formed parts. The results showed that the maximum size of the second phase in this alloy was less than 0.5μm, the second phase area fraction was 0.06%, the DSC curve showed no endothermic peak in the 450~850℃ range, the average width of the columnar crystals was 42μm, the equiaxed crystal ratio was 58%, the Al / Ti composition deviation was 2.2%, the Laves / σ phase area fraction was 0.08%, the defect area fraction was 0.12%, the tensile strength was 685MPa, and the elongation was 32%.
[0053] Example 2 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 20.0%, Fe 71.2%, Y 0.003%, Nb 0.5%, Zr 0.05%, Hf 0.2%, Ti 0.1%, Ta 0.2%, W 0.008%, B 0.002%, C 0.2%, Co 0.5%, Mo 2.0%, and Cr 5.0%. Raw materials included pure nickel, pure iron, Ni-Y master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Hf master alloys, Ni-Ti master alloys, Ni-Ta master alloys, Ni-W master alloys, Ni-B master alloys, Ni-C master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1580℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. SLM forming was used with a laser power of 320W and a scanning speed of 900mm / s. The compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were measured in the SLM-formed parts. The results showed that the maximum size of the second phase in the alloy was less than 0.6μm, the second phase area fraction was 0.12%, the DSC curve showed no endothermic peak in the 450~850℃ range, the average width of the columnar crystals was 38μm, the equiaxed crystal ratio was 52%, the Al / Ti composition deviation was 1.7%, the Laves / σ phase area fraction was 0.15%, the defect area fraction was 0.18%, the tensile strength was 625MPa, and the elongation was 28%.
[0054] Example 3 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 23.0, Fe 61.9, Nd 0.01, Nb 0.1, Zr 0.3, Hf 1.0, Ti 0.467, Ta 0.633, W 0.015, B 0.008, Co 0.5, Mo 2.0, and Cr 10.0. Raw materials included pure nickel, pure iron, Ni-Nd master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Hf master alloys, Ni-Ti master alloys, Ni-Ta master alloys, Ni-W master alloys, Ni-B master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1600℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. Precision casting was employed, with a pouring temperature of 1550℃ and a mold preheating temperature of 900℃. The castings underwent compositional homogeneity testing, statistical analysis of the columnar / equiaxed crystal ratio, and determination of the area fraction of harmful phases. The test results showed that the maximum size of the second phase in this alloy was less than 0.8 μm, with an area fraction of 0.22%. The DSC curve showed no endothermic peak in the 450–850℃ range. The average width of the columnar crystals was 32 μm, the equiaxed crystal ratio was 42%, the Al / Ti composition deviation was 0.8%, the Laves / σ phase area fraction was 0.28%, the defect area fraction was 0.25%, the tensile strength was 580 MPa, and the elongation was 33%.
[0055] Example 4 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 22.0, Fe 75.0, Ce 0.003, Y 0.003, Nd 0.003, Nb 0.1, Zr 0.02, Ti 0.05, B 0.0005, C 0.01, Co 0.02, Mo 1.0, and Cr 1.0. Raw materials included pure nickel, pure iron, Ni-Ce, Ni-Y, Ni-Nd master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Ti master alloys, Ni-B master alloys, Ni-C master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1560℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was used to test the compositional uniformity, statistically analyze the columnar / equiaxed crystal ratio, and determine the area fraction of harmful phases in the SLM-formed parts. The test results showed that the maximum size of the second phase in this alloy was less than 0.5 μm, the area fraction of the second phase was 0.08%, the DSC curve showed no endothermic peak in the 450–850 °C range, the average width of the columnar crystals was 48 μm, the equiaxed crystal ratio was 65%, the Al / Ti compositional deviation was 0.6%, the Laves / σ phase area fraction was 0.10%, the defect area fraction was 0.10%, the tensile strength was 567 MPa, and the elongation was 35%.
[0056] Example 5 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 68.035, Fe 20.0, Sc 0.0015, Nb 0.5, Zr 0.05, Hf 0.1, Ti 0.1, W 0.005, B 0.001, C 0.2, Co 0.5, Mo 2.5, and Cr 8.0. Raw materials included pure nickel, pure iron, Ni-Sc master alloy, Ni-Nb master alloy, Ni-Zr master alloy, Ni-Hf master alloy, Ni-Ti master alloy, Ni-W master alloy, Ni-B master alloy, Ni-C master alloy, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1570℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. Precision casting was used to test the compositional uniformity, statistically analyze the columnar / equiaxed crystal ratio, and determine the area fraction of harmful phases in the casting. The results showed that the maximum size of the second phase in this alloy was less than 0.6 μm, the area fraction of the second phase was 0.10%, the DSC curve showed no endothermic peak in the 450–850 °C range, the average width of the columnar crystals was 35 μm, the equiaxed crystal ratio was 55%, the Al / Ti composition deviation was 1.9%, the Laves / σ phase area fraction was 0.12%, the defect area fraction was 0.15%, the tensile strength was 612 MPa, and the elongation was 30%.
[0057] Example 6 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 38.0, Fe 51.1, Gd 0.005, Nb 1.0, Zr 0.2, Hf 0.5, Ti 0.3, Ta 0.8, W 0.01, B 0.005, C 0.5, Co 1.0, Mo 3.0, and Cr 3.0. Pure nickel, pure iron, Ni-Gd master alloys, and corresponding master alloys were used as raw materials. The alloy was vacuum induction melted at 1590℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. SLM forming was used, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were determined for the SLM-formed parts. The test results show that the maximum size of the second phase of the alloy is less than 0.7 μm, the area fraction of the second phase is 0.18%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 30 μm, the proportion of equiaxed crystals is 48%, the Al / Ti composition deviation is 2.9%, the area fraction of Laves / σ phase is 0.22%, the area fraction of defects is 0.22%, the tensile strength is 576 MPa, and the elongation is 35%.
[0058] Example 7 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 30.0%, Fe 68.5%, Ce 0.1%, Nb 0.2%, Zr 0.02%, Hf 0.11%, Ti 0.05%, Ta 0.05%, B 0.0005%, C 0.01%, Co 0.05%, Mo 0.2%, and Cr 0.3%. Raw materials included pure nickel, pure iron, Ni-Ce master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Hf master alloys, Ni-Ti master alloys, Ni-Ta master alloys, Ni-B master alloys, Ni-C master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1540℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. Precision casting was used to test the compositional uniformity, statistically analyze the columnar / equiaxed crystal ratio, and determine the area fraction of harmful phases in the casting. The results showed that the maximum size of the second phase in this alloy was less than 0.5 μm, the area fraction of the second phase was 0.07%, the DSC curve showed no endothermic peak in the 450–850 °C range, the average width of the columnar crystals was 45 μm, the equiaxed crystal ratio was 62%, the Al / Ti composition deviation was 2.6%, the Laves / σ phase area fraction was 0.09%, the defect area fraction was 0.11%, the tensile strength was 710 MPa, and the elongation was 24%.
[0059] Example 8 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 35.0, Fe 60.0, Y 0.008, Nb 0.1, Zr 0.01, Ti 0.8, Ta 2.5, W 0.018, B 0.009, C 1.2, Co 0.05, Mo 0.1, and Cr 0.1. Raw materials included pure nickel, pure iron, Ni-Y master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Ti master alloys, Ni-Ta master alloys, Ni-W master alloys, Ni-B master alloys, Ni-C master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1610℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was employed, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were determined for the SLM-formed parts. The test results show that the maximum size of the second phase of the alloy is less than 0.7 μm, the area fraction of the second phase is 0.60%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 28 μm, the proportion of equiaxed crystals is 45%, the Al / Ti composition deviation is 1.5%, the area fraction of Laves / σ phase is 0.25%, the area fraction of defects is 0.23%, the tensile strength is 620 MPa, and the elongation is 32%.
[0060] Example 9 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 40.0%, Fe 49.5%, Nd 0.006%, Nb 0.3%, Zr 0.03%, Hf 0.1%, Ti 0.2%, Ta 0.3%, B 0.002%, C 0.2%, Co 0.5%, Mo 4.0%, and Cr 4.5%. Raw materials included pure nickel, pure iron, pure cobalt, pure molybdenum, pure chromium, and Ni-Nd, Ni-Nb, Ni-Zr, Ni-Hf, Ni-Ti, Ni-Ta, Ni-B, and Ni-C master alloys. The alloy was vacuum induction melted at 1570℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. Precision casting was used for forming, and the castings were tested for compositional uniformity, the columnar / equiaxed crystal ratio was statistically analyzed, and the area fraction of harmful phases was determined. The test results show that the maximum size of the second phase of the alloy is less than 0.6 μm, the area fraction of the second phase is 0.14%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 33 μm, the proportion of equiaxed crystals is 50%, the Al / Ti composition deviation is 1.3%, the area fraction of Laves / σ phase is 0.18%, the area fraction of defects is 0.19%, the tensile strength is 550 MPa, and the elongation is 34%.
[0061] Example 10 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 45.0%, Fe 51.14%, Ce 0.004%, Y 0.004%, Nb 0.2%, Zr 0.02%, Ti 0.1%, Ta 0.1%, B 0.001%, C 0.05%, Co 0.3%, Mo 1.5%, and Cr 1.5%. Raw materials included pure nickel, pure iron, Ni-Ce, Ni-Y master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Ti master alloys, Ni-Ta master alloys, Ni-B master alloys, Ni-C master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1560℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was used, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were measured in the SLM-formed parts. The test results showed that the maximum size of the second phase in this alloy was less than 0.6 μm, the second phase area fraction was 0.11%, the DSC curve showed no endothermic peak in the 450–850 °C range, the average width of the columnar crystals was 36 μm, the equiaxed crystal ratio was 54%, the Al / Ti composition deviation was 1.2%, the Laves / σ phase area fraction was 0.14%, the defect area fraction was 0.16%, the tensile strength was 627 MPa, and the elongation was 29%.
[0062] Example 11 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 36.0%, Fe 52.29%, Sc 0.002%, Gd 0.002%, Nb 1.5%, Zr 0.2%, Hf 0.8%, Ti 0.4%, W 0.008%, B 0.004%, C 0.6%, Co 1.5%, Mo 3.0%, and Cr 3.0%. Raw materials included pure nickel, pure iron, Ni-Sc, Ni-Gd master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Hf master alloys, Ni-Ti master alloys, Ni-W master alloys, Ni-B master alloys, Ni-C master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1580℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using FE-SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was used to test the compositional uniformity, statistically analyze the columnar / equiaxed crystal ratio, and determine the area fraction of harmful phases in the SLM-formed parts. The test results showed that the maximum size of the second phase in this alloy was less than 0.7 μm, the area fraction of the second phase was 0.19%, the DSC curve showed no endothermic peak in the 450–850 °C range, the average width of the columnar crystals was 31 μm, the equiaxed crystal ratio was 49%, the Al / Ti compositional deviation was 1.4%, the Laves / σ phase area fraction was 0.20%, the defect area fraction was 0.21%, the tensile strength was 610 MPa, and the elongation was 21%.
[0063] Example 12 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 28.0%, Fe 70.11%, La 0.001%, Sm 0.001%, Dy 0.001%, Nb 0.1%, Zr 0.01%, Ti 0.2%, Ta 0.3%, W 0.006%, B 0.002%, C 0.3%, Co 0.05%, Mo 0.2%, and Cr 0.5%. Raw materials included pure nickel, pure iron, Ni-La, Ni-Sm, Ni-Dy master alloys, and corresponding master alloys. The alloy was vacuum induction melted at 1550℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. Precision casting was used for forming, and the castings were subjected to compositional homogeneity testing, columnar / equiaxed crystal ratio statistics, and harmful phase area fraction determination. The test results show that the maximum size of the second phase of the alloy is less than 0.5 μm, the area fraction of the second phase is 0.09%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 50 μm, the proportion of equiaxed crystals is 68%, the Al / Ti composition deviation is 1.5%, the area fraction of Laves / σ phase is 0.11%, the area fraction of defects is 0.09%, the tensile strength is 630 MPa, and the elongation is 25%.
[0064] Example 13 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 25.0, Fe 66.7, Ce 0.001, Y 0.001, Nd 0.001, Nb 2.0, Zr 0.4, Hf 1.5, Ti 0.6, Ta 2.0, W 0.012, B 0.006, C 0.01, Co 0.1, Mo 1.0, and Cr 1.0. Raw materials included pure nickel, pure iron, Ni-Ce, Ni-Y, Ni-Nd master alloys, and corresponding master alloys. The alloy was vacuum induction melted at 1590℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was employed, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were determined for the SLM-formed parts. The test results show that the maximum size of the second phase of the alloy is less than 0.6 μm, the area fraction of the second phase is 0.23%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 26 μm, the proportion of equiaxed crystals is 43%, the Al / Ti composition deviation is 2.2%, the area fraction of Laves / σ phase is 0.26%, the area fraction of defects is 0.24%, the tensile strength is 650 MPa, and the elongation is 26%.
[0065] Example 14 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 55.0%, Fe 41.3%, Sc 0.001%, Nb 0.2%, Zr 0.02%, Hf 0.01%, Ti 0.08%, Ta 0.1%, W 0.006%, B 0.001%, C 0.05%, Co 0.1%, Mo 0.8%, and Cr 2.0%. Pure nickel, pure iron, Ni-Sc master alloys, and corresponding master alloys were selected as raw materials. The alloy was vacuum induction melted at 1560℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. Precision casting was used to test the compositional uniformity of the castings, statistically analyze the columnar / equiaxed crystal ratio, and determine the area fraction of harmful phases. The test results show that the maximum size of the second phase of the alloy is less than 0.6 μm, the area fraction of the second phase is 0.07%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 40 μm, the proportion of equiaxed crystals is 60%, the Al / Ti composition deviation is 2.7%, the area fraction of Laves / σ phase is 0.09%, the area fraction of defects is 0.13%, the tensile strength is 695 MPa, and the elongation is 24%.
[0066] Example 15 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 60.0%, Fe 32.79%, Y 0.02%, Nb 3.0%, Zr 0.5%, Hf 2.0%, Ti 0.1%, B 0.001%, Co 0.1%, Mo 0.5%, and Cr 1.0%. Raw materials included pure nickel, pure iron, Ni-Y master alloys, Ni-Nb master alloys, Ni-Zr master alloys, Ni-Hf master alloys, Ni-Ti master alloys, Ni-B master alloys, pure cobalt, pure molybdenum, and pure chromium. The alloy was vacuum induction melted at 1570℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect second-phase characteristics and thermal effects. SLM forming was employed, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were determined for the SLM-formed parts. The test results show that the maximum size of the second phase of the alloy is less than 0.5 μm, the area fraction of the second phase is 0.24%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 28 μm, the proportion of equiaxed crystals is 46%, the Al / Ti composition deviation is 1.1%, the area fraction of Laves / σ phase is 0.26%, the area fraction of defects is 0.21%, the tensile strength is 700 MPa, and the elongation is 23%.
[0067] Example 16 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 58.0, Fe 34.6, Nd 0.005, Nb 0.2, Zr 0.02, Ti 1.0, Ta 3.0, W 0.02, B 0.01, C 1.5, Co 0.1, Mo 0.5, and Cr 1.0. Pure nickel, pure iron, Ni-Nd master alloys, and corresponding master alloys were selected as raw materials. The alloy was vacuum induction melted at 1580℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. SLM forming was used, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were determined for the SLM-formed parts. The test results show that the maximum size of the second phase of the alloy is less than 0.6 μm, the area fraction of the second phase is 0.21%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 30 μm, the proportion of equiaxed crystals is 48%, the Al / Ti composition deviation is 1.0%, the area fraction of Laves / σ phase is 0.24%, the area fraction of defects is 0.20%, the tensile strength is 640 MPa, and the elongation is 27%.
[0068] Example 17 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 52.4%, Fe 31.68%, Gd 0.003%, Nb 0.2%, Zr 0.02%, Hf 0.179%, Ti 0.1%, B 0.001%, Co 3.0%, Mo 6.0%, and Cr 6.0%. Pure nickel, pure iron, Ni-Gd master alloys, and corresponding master alloys were selected as raw materials. The alloy was vacuum induction melted at 1590℃ under argon protection, and then refined and atomized into powder. The powder was analyzed using SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. Precision casting was employed to test the compositional uniformity of the castings, statistically analyze the columnar / equiaxed crystal ratio, and determine the area fraction of harmful phases. The test results show that the maximum size of the second phase of the alloy is less than 0.7 μm, the area fraction of the second phase is 0.30%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 25 μm, the proportion of equiaxed crystals is 41%, the Al / Ti composition deviation is 0.8%, the area fraction of Laves / σ phase is 0.34%, the area fraction of defects is 0.27%, the tensile strength is 702 MPa, and the elongation is 16%.
[0069] Example 18 The alloy was precisely formulated according to mass percentages, with the following composition: Ni 56.0, Fe 33.75, Sc 0.003, Nb 0.8, Zr 0.1, Hf 0.3, Ti 0.4, Ta 0.8, W 0.008, B 0.003, C 0.6, Co 1.0, Mo 2.0, and Cr 4.0. Pure nickel, pure iron, Ni-Sc master alloys, and corresponding master alloys were selected as raw materials. The alloy was vacuum induction melted at 1580℃ under argon protection, and then refined and atomized into powder. The powder was analyzed by SEM, EDS, and DSC to detect the characteristics of the second phase and thermal effects. SLM forming was used, and the compositional uniformity, columnar / equiaxed crystal ratio, and harmful phase area fraction were determined for the SLM-formed parts. The test results show that the maximum size of the second phase of the alloy is less than 0.5 μm, the area fraction of the second phase is 0.14%, the DSC curve has no endothermic peak in the range of 450~850℃, the average width of columnar crystals is 38 μm, the proportion of equiaxed crystals is 52%, the Al / Ti composition deviation is 1.6%, the Laves / σ phase area fraction is 0.19%, the defect area fraction is 0.17%, the tensile strength is 587 MPa, and the elongation is 27%.
[0070] Table 1 As shown in Table 1, the experimental results of the various embodiments and comparative examples reveal that the maximum size of the second phase in the microstructure of each embodiment is less than 1 μm and the area fraction is less than 1%. DSC analysis shows no endothermic peak of the rare earth second phase in the 450–850℃ range. This indicates that the present invention, by introducing solid solution regulating elements such as Nb, Zr, and Hf, effectively breaks through the solid solubility limits of rare earth Ce, Y, Gd, Nd, and Sc in a nickel-iron matrix and suppresses the formation of high-melting-point rare earth intermetallic compounds. Furthermore, in the embodiments incorporating La, Sm, Dy, and Ti, Ta, W, B, C, and N, the average width of columnar crystals is 25–50 μm, and the proportion of equiaxed crystals reaches 41%–68%, significantly better than the comparative examples. This demonstrates that the proportion of columnar crystals is effectively reduced and the grains are refined through compositional supercooling and heterogeneous nucleation effects. In the examples where the Co, Mo, and Cr ratios were optimized, the relative deviations of Al and Ti components were ≤3%, and the total area fraction of Laves and σ phases was ≤0.5%, significantly better than the comparative example. This demonstrates that the optimized design of this patent results in a more uniform distribution of solute atoms and delays the precipitation of harmful phases. Simultaneously, the defect area fraction in the additively manufactured and precision-cast parts was 0.09% to 0.27%, the tensile strength reached 550 to 710 MPa, and the elongation was 16% to 35%, showing significantly better overall performance than the comparative example.
[0071] In summary, the nickel-iron alloy system with high rare earth solid solubility, controllable microstructure, and uniform composition provided by this invention can be widely adapted to advanced manufacturing processes such as additive manufacturing, precision casting, and powder metallurgy. Its finished parts can meet the stringent application requirements of high-performance nickel-iron alloy materials in fields such as aero-engines, gas turbines, and nuclear reactors.
[0072] The embodiments of the present invention aim to protect a fine-grained rare-earth nickel-iron alloy with a high isometric crystal ratio, which has the following effects: 1. By introducing solid solution regulating elements such as Nb, Zr, and Hf with specific atomic radii and lattice matching characteristics into the alloy, the solid solution limits of rare earth elements such as Ce, Y, Gd, Nd, and Sc in the nickel-iron matrix are significantly broken. This allows rare earth elements to exist in a fully solid solution state or as fine and dispersed second phases with a size of less than 2 μm and an area fraction of no more than 1%. DSC detection shows no endothermic melting peak of rare earth second phase in the range of 450℃ to 850℃, thus effectively avoiding the formation of micron-sized high-melting-point rare earth second phases in conventional processes. This reduces defects such as incomplete fusion and porosity in additive manufacturing, precision casting, and powder metallurgy processes, and significantly improves the density and high-temperature mechanical reliability of components. 2. By rationally adding rare earth elements such as La, Sm, and Dy, as well as grain-regulating elements such as Ti, Ta, W, B, and C, and utilizing compositional supercooling and heterogeneous nucleation effects, the average width of columnar crystals after alloy solidification is controlled within 50 μm, and the proportion of equiaxed crystals reaches more than 40%, resulting in a fine-grained microstructure with a high proportion of equiaxed crystals. This significantly reduces the anisotropy of mechanical properties caused by coarse columnar crystals and improves the service stability and overall reliability of components under complex stress conditions. 3. By optimizing the addition ratios of Co, Mo, and Cr to meet the requirements of Co:Mo = 1:2~1:10, Co:Cr = 1:2~1:20, and Mo:Cr = 1:1~1:5, the distribution coefficients of Al and Ti during solidification were effectively controlled. This ensured that the relative deviation of Al and Ti composition between any two points in the alloy did not exceed 3%, while the total area fraction of harmful segregated phases such as Laves phase and σ phase was controlled below 0.5%. This significantly improved the compositional uniformity of the alloy, delayed the precipitation kinetics of harmful phases, and thus enhanced the high-temperature creep performance and long-term service stability of the alloy.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A fine-grained rare-earth nickel-iron alloy with a high isometric crystal ratio, characterized in that, The fine-grained rare earth nickel-iron alloy has a composition of Ni-Fe-RE-M, where RE is one or more of Ce, La, Sm, Dy, Y, Gd, Nd and Sc, and M is one or more of Nb, Zr, Hf, Ti, Ta, W, B, C, Co, Mo and Cr; The Ni content ranges from 20.0 wt.% to 75.0 wt.%, the Fe content ranges from 20.0 wt.% to 75.0 wt.%, the total RE content ranges from 0.001 wt.% to 0.1 wt.%, and the total M content ranges from 0.7 wt.% to 15.5 wt.%. The columnar crystals of the fine-grained rare-earth nickel-iron alloy have an average width of ≤50μm and an equiaxed crystal ratio of ≥40%.
2. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to claim 1, characterized in that, In the fine-grained rare-earth nickel-iron alloy, rare earth elements exist in a fully dissolved state or in a dissolved state coexisting with a fine, dispersed second phase.
3. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to claim 2, characterized in that, When a rare earth second phase is present, the size of the second phase is <2μm, the average area fraction is ≤1%, and any 1mm 2 Within the alloy region, the quantity of the second phase varies by no more than 10%.
4. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to claim 1, characterized in that, The relative deviation of Al and Ti composition between any two points in the fine-grained rare-earth nickel-iron alloy is ≤3%, and the total area fraction of harmful segregating phases Laves phase and σ phase is ≤0.5%.
5. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to claim 1, characterized in that, When the fine-grained rare-earth nickel-iron alloy was detected by differential scanning calorimetry, no endothermic melting peak of the rare-earth second phase was observed in the temperature range of 450℃ to 850℃.
6. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to claim 1, characterized in that, The RE is one or more of Ce, Y, and Nd; The total RE content is 0.003 wt.%~0.02 wt.%.
7. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to any one of claims 1-6, characterized in that, M is one or more of Nb, Zr, and Hf; The Nb content is 0.1 wt.%~3.0 wt.%, the Zr content is 0.01 wt.%~0.5 wt.%, and the Hf content is 0.01 wt.%~2 wt.%.
8. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to any one of claims 1-6, characterized in that, M is one or more of Ti, Ta, W, B, and C; The Ti content is 0.05 wt.%~1 wt.%, the Ta content is 0.05 wt.%~3 wt.%, the W content is 0.005 wt.%~0.02 wt.%, the B content is 0.0005 wt.%~0.01 wt.%, and the C content is 0.01 wt.%~1.5 wt.%.
9. The fine-grained rare-earth nickel-iron alloy with a high isoaxial grain ratio according to any one of claims 1-6, characterized in that, M is one or more of Co, Mo, and Cr; The Co content is 0.01 wt.%~3 wt.%, the Mo content is 0.02 wt.%~6 wt.%, and the Cr content is 0.02 wt.%~10 wt.%, with Co:Mo = 1:2~1:10, Co:Cr = 1:2~1:20, and Mo:Cr = 1:1~1:5.